Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kinerja Guru SD Al-Muttaqin di Kota Tasikmalaya - Lintan Nurhalisah; Kusuma Agdhi Rahwana; Arga Sutrisna (CV. Ulil Albab Corp, 2022)
This study aims to determine and analyze the effect of compensation and work environment on performance (a survey of elementary school teachers at Al- Mutaqqin Foundation, Tasikmalaya City). The method used in this study is causality through a census approach. With a research sample of 68 elementary school teachers, Al-Mutaqqin Foundation, Tasikmalaya City. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that compensation has a very good assessment classification, the work environment has a very good assessment classification, while employee performance has a good classification for elementary school teachers at Al-Mutaqqin Foundation, Tasikmalaya City. Taken together, compensation and work environment have a significant effect on employee performance at the Al-Mutaqqin Foundation Elementary School Teacher, Tasikmalaya City. Partially, compensation has a significant effect on employee performance at the Al-Mutaqqin Foundation Elementary School Teacher, Tasikmalaya City. Partially, the work environment has a significant effect on employee performance at the Al-Mutaqqin Foundation Elementary School Teacher, Tasikmalaya City